Pengaruh Pengendalian Internal, Ketaatan Aturan Akuntansi, Moralitas Manajemen dan Budaya Organisasi Terhadap Kecurangan Akuntansi - Rodiah, Siti; Ardianni, Ika; Herlina, Aftania (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
The purpose of this study was to examine the study of internal control, compliance with accounting rules, management morality and organizational culture towards accounting fraud. The population in this study are all employees at the Regional Financial and Asset Management Agency (BPKAD) Office in Riau Province. The sample of this study was 109 respondents. The sampling method in this study was random sampling. The data used in this study is primary data, which is done using a survey method with questionnaires. The processing method carried out is multiple linear regression. Based on the results of the study, it can be concluded that the variables of internal control, compliance with accounting rules and organizational culture negatively affect accounting fraud. While the management morality variable does not affect accounting fraud.